At the Juncture of Administrative Evil and Administrative Racism: The Obstacles and Opportunities for Public Administrators in the United States to Uphold Civil Rights in the Twenty‐First Century. - Williams, Brian N.; Duckett, Brendin (Public Administration Review)
We use a case‐study approach to examine the obstacles and opportunities for public administrators who seek to uphold the civil and human rights of residents in the United States during the twenty‐first century. In particular, our analysis of two cases—one historical and the other contemporary—reveals what occurs at the juncture of administrative evil and administrative racism, where politicians, policymakers, and those who implement policies engage in intentional and functional acts that harm marginalized populations. These actions, which discriminate against and oppress people and communities of color, are antithetical to the core ideals of American democracy and the central tenet of contemporary public administration: social equity. We conclude by offering practical and pedagogical prescriptions to strengthen social equity for all members of the American public in the hope of achieving Martin Luther King's dream of a Beloved Community.